Traffic, Air Pollution, and Distributional Impacts in Dar es Salaam : A Spatial Analysis with New Satellite Data - Dasgupta, Susmita; Wheeler, David; Lall, Somik; Wheeler, David (World Bank, Washington, DC, 2020)
Air pollution from vehicular traffic is a major source of health damage in urban areas. The problems of urban traffic and pollution are essentially geographic, because their incidence and impacts depend on the spatial distribution of economic activities, households, and transport links. This paper uses satellite images to investigate the spatial dynamics of vehicle traffic, air pollution, and exposure of vulnerable residents in the Dar es Salaam metro region of Tanzania. The results highlight significant impacts of seasonal weather (temperature, humidity, and wind-speed factors) on the spatial distribution and intensity of air pollution from vehicle emissions. These effects on the metro region's air quality vary highly by area. During seasons when weather factors maximize pollution, the worst exposure occurs in areas along the wind path of high-traffic roadways. The research identifies core areas where congestion reduction would yield the greatest exposure reduction for children and the elderly in poor households.